Manipulating biochemical pathways in rice - Goddard, Maria Nadia (2004)
The brown planthopper, Nilaparvata lugens, is a pest of rice in tropical regions. Its direct feeding results in loss in yield and plant death ("hopper bum"). Several compounds that stimulate insect attraction have been detected in rice plants colonised by N. lugens, including 1,2-dimethoxybenzene or veratrole. Electro-physiological studies and highresolution gas chromatography have identified veratrole as an attractant of N. lugens. Veratrole is a product of salicylic acid, a derivative of the phenyl propanoid pathway. Salicylic acid is decarboxylated to catechol, a step which is encoded by salicylate hydroxylase. Catechol is subsequently methylated to veratrole, which is released as a volatile compound from rice leaves.